The millennium link the rehabilitation of the Forth & Clyde and Union Canals : proceedings of the international conference organized by the Institution of Civil Engineers and held in Edinburgh, UK, on 30 June-1 July 2000 - Fleming, George (Thomas Telford, 2000)
This volume contains the proceedings of the international conference held by the Institution of Civil Engineers to mark the regeneration of the historic Forth & Clyde and Union Canals.
Keywords: Forth and Clyde Canal (Scotland) -- Congresses.; Union Canal (Scotland) -- Congresses.; Canals -- Scotland -- Maintenance and repair -- Congresses.; elektronické knihy; electronic books